2014
DOI: 10.1177/0898264314553895
|View full text |Cite
|
Sign up to set email alerts
|

Are There Racial-Ethnic Disparities in Time to Pressure Ulcer Development and Pressure Ulcer Treatment in Older Adults After Nursing Home Admission?

Abstract: Objective The objective of this study was to assess whether there are racial and ethnic disparities in the time to development of a pressure ulcer and number of pressure ulcer treatments in individuals aged 65 and older after nursing home admission. Method Multi-level predictors of time to a pressure ulcer from three national surveys were analyzed using Cox proportional hazards regression for White Non-Hispanic residents. Using the Peters–Belson method to assess for disparities, estimates from the regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 35 publications
1
21
1
Order By: Relevance
“…We have previously reported that the characteristics of older adult admissions in this set of NHs are comparable to those in all Medicare/Medicaid certified NHs in the U. S. in the same time period (Bliss et al, 2015). The average age of admissions was approximately 80 years old with APIs and Whites among the oldest.…”
Section: Resultsmentioning
confidence: 65%
“…We have previously reported that the characteristics of older adult admissions in this set of NHs are comparable to those in all Medicare/Medicaid certified NHs in the U. S. in the same time period (Bliss et al, 2015). The average age of admissions was approximately 80 years old with APIs and Whites among the oldest.…”
Section: Resultsmentioning
confidence: 65%
“…Our analysis revealed that African Americans had higher rates of recurrence. Previous reports have noted that African Americans have higher rates of pressure ulcer development 26 28 and display a noted increase in pressure ulcer recurrence after initial healing. 29 Poorer clinical and surgical outcomes in African Americans is a well-documented occurrence across different surgical specialties, 30 , 31 but the relationship remains poorly understood and is likely due to the interplay of multiple factors.…”
Section: Discussionmentioning
confidence: 92%
“…Procedures are described in more detail elsewhere. 31 The sociodemographic and socioeconomic characteristics of the communities in the US Census tracts of the nursing homes included the proportions or percentages of the community that was female or male under < 65 years or ≥65 years old, part of a racial or ethnic minority group, completed 1–8 years or 9–16 years of education, and resided in an urban or rural area. Others community level variables included the proportion of the tract that was working class or below poverty level, as well as the median home value in the tract.…”
Section: Methodsmentioning
confidence: 99%